Costs, benefits and quality of apprenticeships - a regional case study : chapter 15 - Rauner, Felix [Verfasser]; Heinemann, Lars [Verfasser]; Piening, Dorothea [Verfasser]; Bischoff, Rainer [Verfasser] (My University, 2010)
"The QEK (Qualität, Erträge, Kosten - quality, returns, costs) self-evaluation tool allows companies to assess the cost-effectiveness as well as the quality of apprenticeships. Analysing the results of more than 100 companies taking part, we found that, on average, apprenticeships produce net returns. Furthermore, there is a positive correlation between quality and cost-effectiveness. The higher the quality, the better the cost-effectiveness." (Autorenreferat, BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; L 6 Qualität; S 4.3.3 Effizienz & Effektivität des Berufsbildungswesens; L 6.2.3 Evaluation; I 2.1.2.9 Bremen; Betriebliche Berufsausbildung; Qualität; Effizienz; Rentabilität; Kosten-Nutzen-Relation; Selbstevaluation; Fallstudie; Region; Bremen